Analisis Penegakan Integritas dan Etika Aparatur Sipil Negara dalam Pelayanan Publik: Studi Kasus Kantor Lurah 5 Ilir Kota Palembang - Edi Wakhyudin, Selsyah Saputri; Alifah, Farah Nur; Sirli Dwianda; Shabira Aisyah; Dhealinda Jasmine; Rinda Yosika; Mila Angellina; Trifia Agusmi; Vinnisha Tria; Riza Adelia Suryani; M. Firza Wendhika (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the implementation of integrity and ethics among Civil Servants (ASN) in public service delivery at the 5 Ilir Subdistrict Office in Palembang City. The 5 Ilir area, which is located in an urban setting with high population density and dynamic socio-economic activities, requires subdistrict officials to provide fast, responsive, and citizen-oriented services. The study adopts a qualitative approach using purposive sampling, designating the Head of the Subdistrict as the key informant. Data were collected through semi-structured interviews, direct observation of administrative service processes, and document analysis. Data analysis was conducted using a descriptive qualitative method to identify practices, values, and mechanisms related to the enforcement of integrity and ethics in public services. The results indicate that the implementation of integrity and ethics at the 5 Ilir Subdistrict Office is reflected in transparent standard operating procedures, an open queuing system, routine briefings, internal and external supervision mechanisms, and responsive leadership in addressing community issues, including the resolution of social conflicts and flood mitigation. The existence of a legal aid post further strengthens public access to justice. The enforcement of integrity is not merely normative but is systematically implemented through regulations, organizational culture, and oversight mechanisms. This study recommends strengthening the digitalization of public services as a strategy to enhance transparency, accountability, and service quality at the subdistrict level.